1997
DOI: 10.1086/514096
|View full text |Cite
|
Sign up to set email alerts
|

RecombinantMycobacterium tuberculosisKatG(S315T) Is a Competent Catalase‐Peroxidase with Reduced Activity toward Isoniazid

Abstract: The presence of KatG(S315T), a mutation frequently detected in clinical isolates of Mycobacterium tuberculosis, has been associated with loss of catalase-peroxidase activity and resistance to isoniazid therapy. Wild-type KatG and KatG(S315T) were expressed in a heterologous host (Escherichia coli) and purified to homogeneity, and enzymatic activity was measured. The catalase activity for KatG(S315T) was reduced 6-fold, and its peroxidase activity was decreased <2-fold, compared with the activities for wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
84
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 20 publications
14
84
0
1
Order By: Relevance
“…Both enzymes exhibited saturable catalase activity under the conditions employed for the kinetic study. The k cat (WT KatG, 6000 s Ϫ1 ; KatG(Y229F), 0.1 s Ϫ1 ) and K m values (WT KatG, 2.5 mM; KatG(Y229F), 40 mM) are within the ranges reported for these two enzymes (47,51), with minor differences being attributed to either different assay conditions (pH, temperature, and buffer) or differences in the recombinant enzymes used in the various studies. Overall, however, the result that catalase activity is severely disrupted for KatG(Y229F) versus that in WT KatG (k cat /K m ϳ 10 6 lower) is consistent with literature observations (25,27,47) that the Met-Tyr-Trp crosslink is essential for catalatic activity.…”
Section: Uv-visible Spectroscopy Of Wt Katg and Katg(y229f)-supporting
confidence: 59%
See 1 more Smart Citation
“…Both enzymes exhibited saturable catalase activity under the conditions employed for the kinetic study. The k cat (WT KatG, 6000 s Ϫ1 ; KatG(Y229F), 0.1 s Ϫ1 ) and K m values (WT KatG, 2.5 mM; KatG(Y229F), 40 mM) are within the ranges reported for these two enzymes (47,51), with minor differences being attributed to either different assay conditions (pH, temperature, and buffer) or differences in the recombinant enzymes used in the various studies. Overall, however, the result that catalase activity is severely disrupted for KatG(Y229F) versus that in WT KatG (k cat /K m ϳ 10 6 lower) is consistent with literature observations (25,27,47) that the Met-Tyr-Trp crosslink is essential for catalatic activity.…”
Section: Uv-visible Spectroscopy Of Wt Katg and Katg(y229f)-supporting
confidence: 59%
“…In the only other example of a Tyr-Trp bond, CcP(H52Y) (73), the histidine-to-tyrosine mutation allows for the formation of a C-N bond (as opposed to the C-C bond in M. tuberculosis KatG) between the indolic-N (N⑀1) of Trp 51 and the C⑀1 of Tyr 52 . Poulos and coworkers (73) argue that, given the short lifetimes of protein radicals, two sequential one-electron oxidations by two compound I intermediates (resulting from two enzyme turnovers) yielding the Tyr-Trp bond is unlikely to occur in CcP(H52Y).…”
Section: Fig 10mentioning
confidence: 99%
“…Reports of INH activation in mixtures lacking an external oxidant (4,5,6,9,12,14,15) initially suggested that the peroxidatic process may not be required, but the mixtures of INH, NADH, and KatG would have supported NADH reduction of molecular oxygen to superoxide and low levels of H 2 O 2 (15) to activate the peroxidase reaction.…”
Section: Isonicotinic Acid Hydrazide (Isoniazid or Inh)mentioning
confidence: 99%
“…A multiplicity of methods has been employed to directly and indirectly assay INH activation, including the determination of INH oxidation to isonicotinic acid (9,10), the HPLC assay of INH disappearance (11), the inactivation of InhA in a mixture of InhA and KatG (7,12,13,14), the HPLC detection of IN⅐NAD (4,15), and the direct measurement of IN⅐NAD using its characteristic absorbance at 326 nm (6,7,12,15,16). Reports of INH activation in mixtures lacking an external oxidant (4,5,6,9,12,14,15) initially suggested that the peroxidatic process may not be required, but the mixtures of INH, NADH, and KatG would have supported NADH reduction of molecular oxygen to superoxide and low levels of H 2 O 2 (15) to activate the peroxidase reaction.…”
Section: Isonicotinic Acid Hydrazide (Isoniazid or Inh)mentioning
confidence: 99%
“…One of the most common causes of INH resistance is the Ser305Thr (S305T) mutation and, while remaining significant catalase and peroxidase activities, the [S305T] variant enzyme maintains the equivalent affinity for INH (Musser et al, 1996;Haas et al, 1997;Dobner et al, 1997;Marttila et al, 1998;Wengenack et al, 1997;Heym et al, 1995). The MtKatG [S305N] variant completely lost the ability to convert INH into the InhA inhibitor (Wei et al, 2003).…”
Section: Introductionmentioning
confidence: 99%